Preparation, In-vitro, Ex-vivo, and Pharmacokinetic Study of Lasmiditan as Intranasal Nanoemulsion-based In Situ Gel - Jabir, Saba Abdulhadi; Rajab, Nawal A. (Pharmaceutical Nanotechnology, 2025)
BackgroundLasmiditan (LAS) is a recently developed antimigraine drug and was approved in October, 2019 for the treatment of acute migraines; however, it suffers from low oral bioavailability, which is around 40%.ObjectivesThis study aimed to improve the LAS bioavailability via formulation as nanoemulsion-based in situ gel (NEIG) given intranasally and then compare the traditional aqueous-LAS-suspension (AQS) with the two successful intranasal prepared formulations (NEIG 2 and NEIG 5) in order to determine its relative bioavailability (F-relative) via using rabbits.MethodsTwo successfully prepared nanoemulsion (NE) formulas, a and b, were selected for the incorporation of different percentages of pH-sensitive in situ gelling polymer (Carbopol 934) to prepare NEIGs 1, 2, 3, 4, 5, and 6. The pH, gelation capacity, gel strength, and viscosity were predicted for the prepared NEIGs. The release (in vitro) and the nasal permeation (ex vivo) were determined for NEIG 2 and 5, and then both were subjected to pharmacokinetics in vivo studies. Eighteen male rabbits weighing 2.0 to 2.5 kg were employed in the parallel design study. The body surface area (BSA) normalization method was applied for LAS dose calculation. Serial blood samples were taken out and subjected to drug analysis using the HPLC method previously developed and validated by Kumar et al. Primary pharmacokinetics parameters, including maximum drug concentration in plasma (C-max), time to reach C-max (T-max), and area under the concentration-time curve from time zero to affinity (AUCt0-∞) were calculated. Both NE (a and b), together with NEIG (2 and 5) formulas, were subjected to the stability study. Finally, a nasal ciliotoxicity study was carried out to evaluate the nasal toxicity of developed NEIGs 2 and 5.ResultsThe results showed that NEIGs 2 and 5 could be selected as the optimized NEIGs as both achieved 100% permeation within 20 min and then released within 25 and 35 min, respectively, thus achieving 3.3 folds with higher permeation percentages as compared to the AQS. Both NEIGs 2 and 5 exerted comparable release and permeation values as the corresponding NE a and b with more residence time in order to overcome the normal nasal physiological clearance. The values of C-max, T-max, and AUC0- ∞ for NEIG 2 and NEIG 5 were 8066 ± 242 ng/ml, 0.75 ± 0.05 h, 19616.86 ± 589 ng. h/ml, and 7975.67 ± 239 ng/ml, 1.0 ± 0.05 h, 17912.36 ± 537 ng. h/ml, respectively, compared to the traditional AQS, which is equal to 4181.09 ± 125 ng/ml, 2 ± 0.2 h, and 8852.27 ± 266 ng. h/ml, respectively.It was discovered that NEIGs 2 and 5 had better intranasal delivery of LAS and could significantly (p < 0.05) achieve a higher value of permeability coefficient (3.3 folds) and 2.5 folds improvement in bioavailability when compared to AQS. The NE a, NE b, NEIG2, and NEIG5 formulations showed good stability at various temperatures. According to the nasal ciliotoxicity study, the nasal mucosal membrane, which was treated with NEIG 5, showed irritation with a bit of damage. However, damage was not observed when it was treated with NEIG 2, indicating the biocompatibility of the last one to be selected as the optimum formula.ConclusionNEIG 2 and NEIG 5 are promising new intranasal formulas with a faster onset of action and greater bioavailability than the oral dosage form (AQS). Finally, the selected optimum gold formula that will be ready for further clinical study is NEIG 2.
Keywords: lasmiditan nanoemulsion-based in situ gel (NEIG)